Disability and work: the role of health shocks and childhood circumstances - Maarten Lindeboom; Ana Llena-Nozal; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2006)
This paper focuses on the relation between the onset of disability and employment outcomes. We develop an event history model that includes unscheduled hospitalizations as a measure for unanticipated health shocks and estimate the model on data from the British National Child Development Study (NCDS). We show that such health shocks increase the likelihood of an onset of a disability by around 138%. However, health shocks are relatively rare events and therefore the larger part of observed disability rates result from gradual deteriorations in health. We find no direct effect of health shocks on employment outcomes. Using the health shock as an instrumental variable shows that the onset of a disability at age 25 causally reduces the employment rate at age 40 with around 21 percentage points. Our results show that early childhood conditions are important in explaining adult health and socioeconomic outcomes. Those who have experienced bad conditions during early childhood have higher rates of health deterioration during adulthood, are more likely to become non-employed and suffer from longer spells of non-employment during the course of life.
Keywords: I12; J28; 330; disability; work; health shocks; event-history model; early childhood; Lebenszyklus; Kinder; Krankheit; Erwerbsunfähigkeit; Einkommen; Großbritannien